2019
DOI: 10.5858/arpa.2019-0045-cp
|View full text |Cite
|
Sign up to set email alerts
|

Practice Patterns in Urinary Cytopathology Prior to the Paris System for Reporting Urinary Cytology

Abstract: Context.— The Paris System for Reporting Urinary Cytology has been disseminated since its inception in 2013; however, the daily practice patterns of urinary tract cytopathology are not well known. Objective.— To assess urinary tract cytopathology practice patterns across a variety of pathology laboratories to aid in the implementation and future update of the Paris System for Reporting Urinary Cytology. Design.— A questionnaire was designed to gather information about urinary tract cytopathology practices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The criteria that TPS put forth was based on the evidence that was derived from studies using the liquid‐based ThinPrep (Hologic Inc, Marlborough, Massachusetts) and SurePath (Becton‐Dickinson, Franklin Lakes, New Jersey) preparation methods. However, a recent College of American Pathologists survey found that approximately 40% and 30%, respectively, of US pathology laboratories use ThinPrep and cytospin (Thermo Fisher Scientific, Waltham, Massachusetts) . Several studies in urinary cytology have noted subtle differences in cytological features between aliquots from the same sample processed using both methods .…”
Section: Introductionmentioning
confidence: 99%
“…The criteria that TPS put forth was based on the evidence that was derived from studies using the liquid‐based ThinPrep (Hologic Inc, Marlborough, Massachusetts) and SurePath (Becton‐Dickinson, Franklin Lakes, New Jersey) preparation methods. However, a recent College of American Pathologists survey found that approximately 40% and 30%, respectively, of US pathology laboratories use ThinPrep and cytospin (Thermo Fisher Scientific, Waltham, Massachusetts) . Several studies in urinary cytology have noted subtle differences in cytological features between aliquots from the same sample processed using both methods .…”
Section: Introductionmentioning
confidence: 99%
“…[ 6 ] However; a considerable number of laboratories have maintained the conventional cytospin technique according to the College of American Pathologists Survey. [ 5 ] In this study, we demonstrated the performance characteristics of the second most popular type of preparation in urine cytology.…”
Section: Discussionmentioning
confidence: 98%
“…The Paris Working Committee concluded at their first meeting that TPS has a high sensitivity to HGUC. [ 5 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These classification systems emerged in harmony with the histological classification used for bladder tumors. It is well known that some of the shortcomings of urinary cytopathology, particularly low sensitivity in detecting low-grade non-invasive lesions, make urinary cytology samples one of the more difficult specimens encountered in cytopathology [ 38 , 39 , 40 ]. Difficulties also arise from low cellularity of smears and pre-fixation cellular deterioration.…”
Section: ⧉ Urinary Cytology the Paris Systemmentioning
confidence: 99%